2017
DOI: 10.1007/s10916-017-0839-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Segmentation of Pectoral Muscle on MLO-View Mammogram Using Enhancement Filter

Abstract: The presence of predominant density region of the pectoral muscle in Medio-Lateral Oblique (MLO) view of the mammograms can affect or bias the results of mammograms processing for breast cancer detection using intensity based methods. Therefore, to improve the diagnostic performance of breast cancer detection using computer-aided system, identification and segmentation of pectoral muscle is an important task. This paper presents, an intensity based approach to identify the pectoral region in mammograms. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Although there are many methods developed in the literature, the majority of them were evaluated qualitatively by expert radiologists (Kwok et al, 2004;Chen and Zwiggelaar, 2010) or have been evaluated using their own private datasets. It can be observed in Table 4 that our proposed method outperformed our previous method (Rampun et al, In terms of the false negative and false positive rates obtained with the MIAS dataset, our method produced F N R=3.2% and F P R=0.6%, respectively, which indicated that we quantitatively outperform recent studies (Vikhe and Thool, 2017;Chen et al, 2015;Yoon et al, 2016;Liu et al, 2014). Although the studies of Camilus et al (2010) and Ferrari et al (2004) reported small false positives, their proposed methods produced large false negatives of 5.58% and 5.77%, respectively.…”
Section: Comparative Studysupporting
confidence: 48%
See 4 more Smart Citations
“…Although there are many methods developed in the literature, the majority of them were evaluated qualitatively by expert radiologists (Kwok et al, 2004;Chen and Zwiggelaar, 2010) or have been evaluated using their own private datasets. It can be observed in Table 4 that our proposed method outperformed our previous method (Rampun et al, In terms of the false negative and false positive rates obtained with the MIAS dataset, our method produced F N R=3.2% and F P R=0.6%, respectively, which indicated that we quantitatively outperform recent studies (Vikhe and Thool, 2017;Chen et al, 2015;Yoon et al, 2016;Liu et al, 2014). Although the studies of Camilus et al (2010) and Ferrari et al (2004) reported small false positives, their proposed methods produced large false negatives of 5.58% and 5.77%, respectively.…”
Section: Comparative Studysupporting
confidence: 48%
“…Curve fitting-based techniques (Mustra and Grgic, 2013;Bora et al, 2016;Vikhe and Thool, 2017;Chen et al, 2015) have also been used as a part of the segmentation or post-processing step to estimate the pectoral muscle curve. Mustra and Grgic (2013) manually selected initial points for polynomial fitting to estimate the actual muscle boundary, which they assumed to be concave or convex.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations